Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 584 species occurrences available in GBIF matching the query: { "and" : [ "Year 1960-1990", "Geometry POLYGON((-180 -51,180 -51,180 -49,-180 -49,-180 -51))", "HasCoordinate is true", "TaxonKey is Mammalia", "HasGeospatialIssue is false" ] } The dataset includes 584 records from 19 constituent datasets: 2 records from iNaturalist Research-grade Observations. 23 records from MVZ Mammal Collection (Arctos). 6 records from NMNH Extant Specimen Records. 1 records from Australian National Wildlife Collection provider for OZCAM. 96 records from Australian Museum provider for OZCAM. 4 records from National Whale and Dolphin Sightings and Strandings Database. 1 records from Distribution ashore and breeding places of southern elephant seals. 26 records from Plan de vertebrados de la Patagonia. 21 records from University of Michigan Museum of Zoology, Division of Mammals. 152 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS). 61 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 22 records from Marine biological observation data from coastal and offshore surveys around New Zealand. 50 records from Recopilación de datos e información para el Inventario Nacional de Especies de mamíferos marinos nativos de Chile 2016.. 27 records from KUBI Mammalogy Collection. 35 records from Seabirds of the Southern and South Indian Ocean. 1 records from DMNS Mammal Collection (Arctos). 33 records from Observations de mammifères marins issues des campagnes dans les Terres Australes et Antarctiques Françaises (programme 109 Institut Polaire Français - IPEV). 20 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 3 records from Field Museum of Natural History (Zoology) Mammal Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences